HUBUNGAN PERILAKU MASYARAKAT DENGAN UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA UPT PUSKESMAS KECAMATAN SUMBAWA UNIT II - Julia Mujahadah Pratiwi; Evi Gustia Kesuma; Dewa Gede Sanjaya Putra (Jurnal Kesehatan dan Sains, 2021)
Dengue Hemorrhagic Fever is an infectious disease of the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito and is still one of the health problems that has an increasing number of cases every year. The high incidence of Dengue Hemorrhagic Fever is due to the lack of prevention efforts made by the community. The research has aim to determine the relationship between community behavior and efforts to prevent Dengue Hemorrhagic Fever in the working area of ​​the UPT Puskesmas Sumbawa District Unit II. This research is a quantitative research with cross sectional research design and sampling technique using simple random sampling with a sample of 82 respondents. Data analysis using SPSS version 16.0 with test analysis Spearman Ranks. The results of the study showed that the majority of respondents had enough behavior as much as 42 respondents (51.2%) and the majority of respondents who have prevention efforts are in the sufficient category as many as 45 respondents (54.9%). Bivariate results using test Rank Spearman stated that there was a significant relationship between community behavior and efforts to prevent Dengue Hemorrhagic Fever with a p-value 0.00 (p-value < 0.01). So it can be concluded that there is a relationship between community behavior and efforts to prevent Dengue Hemorrhagic Fever in the work area of ​​the UPT Puskesmas Sumbawa District Unit II.